Evaluation of structural integrity in abandoned school building / Muhammad Afif Asaudi - Asaudi, Muhammad Afif (2024)
The New Economic Policy (NEP) marked a notable surge in educational infrastructure development, prioritizing the enhancement of educational services. The student population continues to grow steadily, leading to a critical shortage of adequate classroom facilities. With the rollout of the Twelfth Malaysia Plan, the government has fully committed to enhancing the infrastructure in the educational sector. Therefore, it is imperative to take steps to utilise abandoned school buildings for reconstruction, which necessitates a structural integrity assessment by combining on-site testing and structural software analysis. This study investigated an abandoned school block to deduce on the structural integrity of the building before reburnish works could be carry out to resume the function of the building to its initial purpose. Both on-site test measurements and structural analysis and modelling were employed in this study. The purpose of this research is to analyse the structural integrity of abandoned school buildings in terms of existing structural strength by implementing the use of Nondestructive Test and Destructive Test techniques to form a consolidated dataset for structural modelling and analysis. Nine locations were tested for compressive strength using a rebound hammer, nineteen samples of concrete structure coring, and six samples of reinforcement steel were tested. The data obtained from the site measurements were utilised to remodel the structure in Prota Structure 2018. The findings showed severe structural issues in abandoned structure under study, with deterioration and deficiencies in strength and insufficient reinforcement areas, violating BS8110-1997 standards. Based on the findings, this research concludes that immediate repairs are essential for the building's stability and compliance with safety standards. This study recommended that a structural strengthening scope is compulsory if the reinstatement of the abandoned school block is necessary. Structural strengthening can be done such as adding additional reinforcement or using fibre-reinforced polymers to enhance load-bearing capacity and ensure safety. The research provides a comprehensive methodology for analysing the structural integrity of abandoned buildings. By following this methodology, one can effectively assess the structural soundness and identify any potential issues.